2012
DOI: 10.1603/en11318
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Emerald Ash Borer (Coleoptera: Buprestidae) and Biotic Factors Affecting Its Immature Stages in the Russian Far East

Abstract: Field surveys were conducted from 2008 to 2011 in the Khabarovsk and Vladivostok regions of Russia to investigate the occurrence of emerald ash borer, Agrilus planipennis Fairmaire, and mortality factors affecting its immature stages. We found emerald ash borer infesting both introduced North American green ash (Fraxinus pennsylvanica Marshall) and native oriental ashes (F. mandshurica Rupr. and F. rhynchophylla Hance) in both regions. Emerald ash borer densities (larvae/m(2) of phloem area) were markedly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 20 publications
3
67
0
1
Order By: Relevance
“…In 2003, researchers began foreign exploration for EAB natural enemies in northeastern China, resulting in the discovery of four hymenopteran parasitoid species: (1) Sclerodermus pupariae Yang and Yao (Bethylidae), an ectoparasitoid of larvae, prepupae, and pupae [58,59]; (2) Spathius agrili Yang (Braconidae), an ectoparasitoid of late-instar larvae [26,60]; (3) Tetrastichus planipennisi Yang (Eulophidae), an endoparasitoid of late-instar larvae [26,61]; and (4) Oobius agrili Zhang and Huang (Encyrtidae), an egg parasitoid [62]. Subsequent EAB natural enemy surveys in the Russian Far East from 2008 to 2012 led to the discovery of three additional species of hymenopteran parasitoid: (5) Spathius galinae Belokobylskij and Strazanac (Braconidae), an ectoparasitoid of late-instar larvae [63,64]; (6) Atanycolus nigriventris Vojnovskaja-Krieger (Braconidae), an ectoparasitoid of late-instar larvae [63,64]; and (7) Oobius primorskyensis Yao and Duan (Encyrtidae), an egg parasitoid [65]. In a more recent EAB natural enemy survey in northeastern China, two species of predacious Coleoptera were found attacking late-instar larvae and pupae of EAB: (8) Tenerus sp.…”
Section: The Role Of Natural Enemies In Suppressing Eab In Its Nativementioning
confidence: 99%
See 4 more Smart Citations
“…In 2003, researchers began foreign exploration for EAB natural enemies in northeastern China, resulting in the discovery of four hymenopteran parasitoid species: (1) Sclerodermus pupariae Yang and Yao (Bethylidae), an ectoparasitoid of larvae, prepupae, and pupae [58,59]; (2) Spathius agrili Yang (Braconidae), an ectoparasitoid of late-instar larvae [26,60]; (3) Tetrastichus planipennisi Yang (Eulophidae), an endoparasitoid of late-instar larvae [26,61]; and (4) Oobius agrili Zhang and Huang (Encyrtidae), an egg parasitoid [62]. Subsequent EAB natural enemy surveys in the Russian Far East from 2008 to 2012 led to the discovery of three additional species of hymenopteran parasitoid: (5) Spathius galinae Belokobylskij and Strazanac (Braconidae), an ectoparasitoid of late-instar larvae [63,64]; (6) Atanycolus nigriventris Vojnovskaja-Krieger (Braconidae), an ectoparasitoid of late-instar larvae [63,64]; and (7) Oobius primorskyensis Yao and Duan (Encyrtidae), an egg parasitoid [65]. In a more recent EAB natural enemy survey in northeastern China, two species of predacious Coleoptera were found attacking late-instar larvae and pupae of EAB: (8) Tenerus sp.…”
Section: The Role Of Natural Enemies In Suppressing Eab In Its Nativementioning
confidence: 99%
“…Ecological studies at field sites in northeast China and the Russian Far East revealed these insect natural enemies cause high mortality of EAB eggs and larvae and play a critical role in suppressing EAB densities in forested areas of Asia [26,64,66,67]. The abundance and contribution of individual species to EAB control varied by geographic region (Table 1).…”
Section: The Role Of Natural Enemies In Suppressing Eab In Its Nativementioning
confidence: 99%
See 3 more Smart Citations